A New Method of Dredging, Applicable to Some Kinds of Mining Operations - Rossiter W. Raymond (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1880)
I DESIRE to call the attention of the Institute to a novel system of dredging, which, it seems to me, may prove applicable, not only to river and harbor improvements, but also to certain varieties at least of alluvial and diluvial gold mining; that is, river-mining, barmining, coast-mining, and any other similar operations now carried on by means of coffer-dams or dredging machines. The simple and effective method to which I refer is the invention of General Roy Stone, formerly an officer of volunteers, and at present a civil engineer, engaged under General Newton, of the United States Engineer Corps, upon the government works in New York harbor. General Stone has been, since September, 1878, in charge of operations upon Diamond Reef. This reef, lying between Governor's Island and the Battery, is one of the most dangerous in the harbor. Its position in the highway of navigation, and the fact that it is dangerous only to vessels of considerable draught and at certain stages of the tide, combine to increase the serious nature of the disasters which it has caused. The reef consists partly of rock in place, and partly of deposits of glacial clay, boulders, and pebbles, over all of which lies, or did lie until it was removed, the ordinary silt and rubbish of the harbor. As the purpose of the present paper has nothing to do with the special dimensions and other circumstances of this particular work, I describe those features only which are connected with General Stone's ingenious device. Various attempts have been made to remove the upper portion of Diamond Reef and secure a navigable depth at low tide. Some years ago Maillefert undertook to accomplish this by firing charges of high explosives, simply laid upon the surface. He accomplished some good in the removal of projecting points and ridges ; but as soon as the surface of the reef had become approximately level, his method was no longer effective. After the work had been taken up by the Engineer Corps, the well-known drilling-scow invented by General Newton was brought into action ; and, so long as holes could be bored and fired in solid rock, this process was effective enough. In the mixture of hard-pan